- 2 ( y - 3 ) = 2 y - 6
- 2 ∙ y - 2 ∙ ( - 3 ) = 2 y - 6
- 2 y + 6 = 2 y - 6
Subtract 2 y to both sides
- 2 y + 6 - 2 y = 2 y - 6 - 2 y
- 4 y + 6 = - 6
Subtract 6 to both sides
- 4 y + 6 - 6 = - 6 - 6
- 4 y = - 12
Divide both sides by - 4
y = - 12 / - 4
y = 3
a. one solution
14. Describe the number of solutions for the equation
-2(y-3) =2y-6
a. one solution
b. no solution
c. infinite solutions
my answer is c. i have a few more questions for this test and if anyone could help me that would be great.
1 answer